Predictors for inadequate knowledge and negative attitude towards childhood immunization among parents in Hulu Langat, Selangor, Malaysia - Che Abdullah, Azreena; Mohd Zulkefli, Nor Afiah; Abdul Manaf, Rosliza (Malaysian Public Health Physicians Association, 2018)
Vaccine hesitancy among parents has led to re-emergence of vaccine preventable diseases. In Malaysia, measles cases had increased by three times in 2015 compared to previous year. Immunization coverage has always been above 95% since 2009. However, in 2014, Mumps-Measles-Rubella (MMR) coverage has a significant drop to 93.4%. The aim of the study was to identify predictors for inadequate knowledge and negative attitude towards childhood immunization among parents in Hulu Langat, Selangor. A cross sectional study design was conducted from January to July 2016 with760 respondents. Respondents were selected by cluster random sampling and a validated self-administered questionnaire was used. The majority of respondents were female (70%), Malay (87%), employed (92%) and parents with tertiary education (99.7%). In this study, 12.8% parents have an inadequate knowledge on childhood immunization and 47.6% parents have a negative attitude towards childhood immunization. The predictors for inadequate knowledge on childhood immunizations were last child’s age of 2 years old or more (AOR=1.413 95% CI 0.28-0.69); parents without tertiary education (AOR=2.02 95% CI 1.15-3.54); parents withouteducational exposure on childhood immunization (AOR=2.87 95% CI 1.59-5.18) and parents who obtained information on childhood immunization from non-healthcare provider (AOR=2.66 95% CI 1.50-4.70). Predictors for negative attitude on childhood immunizations were being male (AOR=1.44 95% CI 1.04-2.01); parents without tertiary education (AOR=1.67 95% CI 1.04-2.68); household income of less than RM5000 (AOR=1.85 95% CI 1.28-2.67) and unsatisfactory religious belief (AOR=2.76 95% CI 2.03-3.75). Therefore, these predictors should be considered in any health intervention on childhood immunizations for parents in Malaysia.